In Search of Meaning: Managing for the Health of Organizations, Our Communities and the Natural WorldIn Search of Meaning: Managing for the Health of Organizations, Our Communities and the Natural World, by PauchantThierry C. and Associates San Francisco: Jossey-Bass. - Fineman, Stephen (Academy of Management Review, 1996)
The article reviews the book ?In Search of Meaning: Managing for the Health of Organizations, Our Communities and the Natural World,? by Thierry C. Pauchant.